1986
DOI: 10.1002/cyto.990070602
|View full text |Cite
|
Sign up to set email alerts
|

Improved high‐affinity monoclonal antibody to lododeoxyuridine

Abstract: Three monoclonal antibodies (Mabs), IU-1, IU-4, and B-44 were evaluated in enzyme immunoassays (ELISA) and by flow cytometry for their abilities to recognize bromodeoxyuridine (BrdUrd)-and iododeoxyuridine (1dUrd)-substituted DNA's, nucleotides, and nucleosides. IU-4 is a new Mab, derived from mice immunized with 5-iodo-2'-deoxyuridine-5'-monophosphate (IdUMP) conjugated through the phosphate group to albumin. This immunogen was selected to resemble IdUMP in DNA. In competition ELISA assays, IU-4 prefers IdUrd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…These factors include the degree of DNA denaturation, the concentration and affinity of monoclonal antibodies, the fluorescent probe used, and the number of fluorescent molecules attached to the secondary antibody. Vanderlaan et al have documented the high affinity of IU-4 with reliable detection of BrdUrd at densities 5 2.5% (11). Loweraffinity monoclonal antibodies might be associated with a lesser degree of BrdUrd concentration independence.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the degree of DNA denaturation, the concentration and affinity of monoclonal antibodies, the fluorescent probe used, and the number of fluorescent molecules attached to the secondary antibody. Vanderlaan et al have documented the high affinity of IU-4 with reliable detection of BrdUrd at densities 5 2.5% (11). Loweraffinity monoclonal antibodies might be associated with a lesser degree of BrdUrd concentration independence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, monoclonal antibodies, Br-3 that recognizes BrdU specifically [4] and IU-4 that recognizes both BrdU and iododeoxyuridine (IUdR) [31], have been developed.…”
mentioning
confidence: 99%
“…They found that the monoclonal antibody B44 (5) was minimally reactive to CldUrd after incubation in a highsalt buffer. To stain CldUrd specifically, they used an antibody with minimal reactivity to IdUrd, similar to the Br3 antibody described previously by Vanderlaan et al (8). Their procedure involved indirect staining of both B44 and the anti-CldUrd-specific antibody.…”
mentioning
confidence: 99%